Criminal Law Policy in an Effort to Make the Criminal Fines Effective - Azisa, Nur; Pratiwi Arifin, Arnita (International Journal of Psychosocial Rehabilitation, 2020)
Criminal law policy is a political law that aims to enable positive criminal law regulations to be formulated better in terms of substance. Criminal fines are the imposition of financial obligations that must be paid by the convicted to the state. Therefore, the regulation needs to be maximized because the fine is included in Non-Tax State Revenue (PNBP). There is one major weakness in the substance of criminal fine regulation. The formulation of criminal sanctions for fines in criminal law legislation does not have the power of execution yet, so there are many cases of unpaid fines and it always lead to imprisonment in lieu of fines. Therefore, criminal law policy needs to transform the Collateral Confiscation (Conservatoir Beslaag) in civil legal system with the aim that criminal fines will be more effective in their execution. Collateral Confiscation at the investigation level can be implemented because criminal fines are debts to be paid (Article 1311 of the Civil Code) so that all movable and immovable properties belonging to the debtor (convicted) become the collateral of debtor’s debt (convicted).